K-State First Residential CAT Communities 2013 - Kansas State University, K-State First (Kansas State University. K-State First., 2013)
A brochure describing Residential Connecting Across Topics (CAT) Communities at Kansas State University for the 2013-2014 academic year. Provided in the brochure is an overview, photographs within different residence halls, and instructions on how to join a Residential CAT Community.
Keywords: Guide; CAT communities; First-year experience program; Learning Assistants; Living-learning communities; Fliers (printed matter)